Emerging drugs for the treatment of onychomycosis. (2nd October 2019) - Gupta, Aditya K.; Stec, Nadia
ABSTRACT: Introduction : Onychomycosis is a widespread nail disease, often occurring on the feet. It is a chronic and often recurring disease, which makes it difficult to eradicate. The infection may be caused by dermatophytes, non-dermatophyte molds, and yeasts. Traditionally, systemic antifungal medications have been used to treat this infection, but in recent years topical formulations have been the focus of research. Areas covered : This review outlines the current antifungal market and novel treatments currently in development or in experimental phases. It highlights a shift from systemic treatments to topical options as well as penetration enhancers. There are also several novel systemic options in development. Expert opinion : Although there have been significant developments in treatment options for onychomycosis, it remains a challenging chronic condition with less than desirable cure rates. This may be attributed to the formation of fungal biofilms and limited understanding of the fungal lifecycle. However, when patients adhere to treatment protocols and employ preventative measures, outcomes are generally favorable.